Decorin suppresses stemness and migration potential of malignant peripheral nerve sheath tumor through inhibiting epidermal growth factor receptor signaling - Jia, Xiaotian; Chen, Lin; Yu, Cong (Biochimica et biophysica acta. Molecular basis of disease, 2024)
Cancer stem cells (CSCs) play pivotal roles in the growth, invasion, metastasis, chemo-resistance in malignant peripheral nerve sheath tumor (MPNST). The current characterization of CSCs in MPNST is not complete. Decorin is a critical regulator of microenvironment, but its expression and function in CSCs of MPNST has not been studied. In the current study, Decorin levels and its relationship with lung and liver metastasis were determined in clinical specimens. Decorin expression in CD133-positive or CD44-positive CSCs was analyzed by RT-qPCR on cytospun MPNST cells after flow cytometry-based cell sorting. Decorin-positive cells were separated from Decorin-negative cells in transfected MPNST cell lines using a designed plasmid expressing red fluorescent protein (RFP) under a Decorin promoter. Tumor sphere formation, tumor growth, cell invasion, cell migration, and the resistance to chemotherapy-induced apoptosis were determined on Decorin-positive versus Decorin-negative MPNST cells. In vivo tumor growth was analyzed in mice receiving subcutaneous transplantation of Decorin-positive versus Decorin-negative MPNSTs. We found that Decorin levels were significantly downregulated in MPNST specimens, compared to non-tumorous adjacent tissue. Significantly lower Decorin levels were detected in MPNSTs with lung or liver metastasis compared to those without. Poorer patient survival was detected in Decorin-low MPNST, compared to Decorin-high subjects. More Decorin-negative cells were detected in CD133-positive MPNST cells than CD133-negative MPNST cells, and in CD44-positive MPNST cells than in CD44-negative MPNST cells. Compared to Decorin-positive MPNST cells, Decorin-negative MPNST cells generated significantly more tumor spheres in culture, were more invasive and migratory, and were more resistant to chemotherapy-induced apoptosis, likely due to the inhibition of epidermal growth factor receptor signaling by Decorin. Decorin-negative MPNST cells grew significantly larger tumor in vivo. Thus, depletion of Decorin may occur in CSCs in MPNSTs, serving possibly as a new therapeutic target. [Display omitted] •Decorin is reduced expression in malignant MPNSTs, particularly in those with lung or liver metastasis.•Lower Decorin levels correlate with poorer patient survival.•Loss of Decorin was observed in CSCs of MPNSTs.•Loss of Decorin likely regulate stemness of CSCs of MPNST cells through EGFR signaling.